Superfrogs in the city: 150 year impact of urbanization and agriculture on the European Common Frog. (25th September 2020) - Niemeier, Stephanie; Müller, Johannes; Struck, Ulrich; Rödel, Mark‐Oliver
Abstract: Despite growing pressure on biodiversity deriving from increasing anthropogenic disturbances, some species successfully persist in altered ecosystems. However, these species' characteristics and thresholds, as well as the environmental frame behind that process are usually unknown. We collected data on body size, fluctuating asymmetry (FA), as well as nitrogen stable isotopes (δ 15 N) from museum specimens of the European Common Frog, Rana temporaria, all originating from the Berlin–Brandenburg area, Germany, in order to test: (a) if specimens have changed over the last 150 years (1868–2018); and (b) if changes could be attributed to increasing urbanization and agricultural intensity. We detected that after the Second World War, frogs were larger than in pre‐war Berlin. In rural Brandenburg, we observed no such size change. FA analysis revealed a similar tendency with lower levels in Berlin after the war and higher levels in Brandenburg. Enrichment of δ 15 N decreased over time in both regions but was generally higher and less variable in sites with agricultural land use. Frogs thus seem to encounter favorable habitat conditions after pollution in postwar Berlin improved, but no such tendencies were observable in the predominantly agricultural landscape of Brandenburg. Urbanization, characterized by the proportion of built‐up area, was not the main associated factor for the observed trait changes. However, we detected a relationship with the amount of urban greenspace. Our study exemplifies that increasing urbanization must not necessarily worsen conditions for species living in urban habitats. The Berlin example demonstrates that public parks and other urban greenspaces have the potential to serve as suitable refuges for some species. These findings underline the urgency of establishing, maintaining, and connecting such habitats, and generally consider their importance for future urban planning. Abstract : We analyzed if body size, fluctuating asymmetry, and nitrogen stable isotopes from museum specimens of the European Common Frog from the Berlin–Brandenburg area, Germany have changed over the last 150 years (1868–2018), and if changes were associated with increasing urbanization and agricultural intensity. After World War II, frogs were larger than in pre‐war Berlin. In rural Brandenburg, we observed no such size change. Enrichment of δ 15 N decreased over time in both regions. Urbanization, characterized by the proportion of built‐up area, was not the main factor for the trait changes. However, there was a relationship with the amount of urban greenspace.